Hungary : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper assesses recent trends in Hungary's potential growth and medium-term growth prospects. It analyzes to what extent the recent moderation of GDP growth reflects structural factors. The paper lays out some stylized facts about the Hungarian economy that could explain the growth slowdown observed in recent years. It provides estimates of potential growth using various methods, identifies the sources of the growth slowdown, and offers forecasts of potential growth over the medium-term under the baseline scenario. A model-based approach is also employed to estimate potential growth over the medium term under a reform scenario.